Excel 2016 Power Programming with VBA - Alexander, Michael 1972-; Kusleika, Dick (John Wiley & Sons, Inc., 2016)
Encompassing an analysis of Excel application development and a complete introduction to Visual Basic for Applications (VBA) - with over 800 pages of tips, tricks, and best practices, this comprehensive book presents all of the techniques you need to develop both large and small Excel applications. --
Includes bibliographical references and index. - Vendor-supplied metadata
Keywords: Microsoft Excel (Computer file); Visual Basic for Applications (Computer program language); Visual programming (Computer science); Business -- Computer programs; Electronic spreadsheets; Programmation visuelle; Tableurs; COMPUTERS; Desktop Applications; Spreadsheets; Business; Computer programs; Excel 2016; VisualBASIC für Applikationen